Correction: Gray whales (Eschrichtius robustus) in San Francisco Bay experience high mortality and have limited affiliation to known foraging groups - Josephine M. Slaathaug; Rebekah S. Lane; William Keener; Alie Pérez; Moe Flannery; Marc A. Webber; Aalea Grimes; Adelle M. Wilkin; Julia E. O’Hern; Pádraig J. Duignan; John Calambokidis; Daniel E. Crocker (Frontiers in Marine Science, 2026)

Ecology and restoration potential of Ruppia maritima in a managed mosquito impoundment of the Indian River Lagoon, Florida, USA - Deanna F. Webber; Richard E. Mulroy; Patrick H. Monaghan; David C. Heuberger; M. Dennis Hanisak; Rachel A. Brewton (Regional Studies in Marine Science, 2026)

Gray whales (Eschrichtius robustus) in San Francisco Bay experience high mortality and have limited affiliation to known foraging groups - Josephine M. Slaathaug; Rebekah S. Lane; William Keener; Alie Pérez; Moe Flannery; Marc A. Webber; Aalea Grimes; Adelle M. Wilkin; Julia E. O’Hern; Pádraig J. Duignan; John Calambokidis; Daniel E. Crocker (Frontiers in Marine Science, 2026)
Terrestrial and marine species are exhibiting distributional shifts due to climate change and resource availability. As food webs are impacted, some species have moved into areas of increased human activity, encountering anthropogenic hazards. A coastal marine species that undertakes a long migration between breeding and foraging ranges, the Eastern North Pacific (ENP) population of gray whales ( Eschrichtius robustus ) is especially vulnerable to changes. Subgroups of ENP gray whales, including the Pacific Coast Feeding Group and the (Puget) Sounders, have adapted to exploit alternative feeding grounds as prey availability declines in the Arctic. Novel to known migration phenology, gray whales have been observed seasonally since 2018 in San Francisco Bay (SF Bay), California. We evaluated subgroup identity and mortality of gray whales in SF Bay from 2018–2025 using photo-identification. Data were collected through vessel-based surveys, opportunistic effort, and community submissions. We identified 114 individual whales of which eight were matched to a subgroup, indicating gray whales utilizing SF Bay are not merely a range extension by foraging subgroups. Only four gray whales were resighted within SF Bay between years. Using photographs, 21 individuals were successfully matched to carcasses and a minimum mortality rate of 18% was determined. Blunt and/or sharp force trauma consistent with vessel strike was determined to be the cause of death for 30 of 70 carcasses, and for nine of 11 matched animals where a cause of death was determined. Sounder and PCFG matched whales were more likely to survive SF Bay than ENP individuals, though minimum length of stay did not influence mortality. This work confirms that gray whales entering SF Bay are highly susceptible to vessel strike mortality and highlights a crucial need to identify and implement adaptive management strategies to mitigate injuries and mortality as whales continue to utilize novel habitat.

Productivity, growth, and biogeochemistry of pelagic Sargassum in a changing world - Brian E. Lapointe; Deanna F. Webber; Rachel A. Brewton (Harmful Algae, 2025)

Evaluation of multimodel averaging approaches for ensembling evapotranspiration and yield simulations from maize models - Viveka Nand; Zhiming Qi; Liwang Ma; Matthew J. Helmers; Chandra A. Madramootoo; Ward N. Smith; Tiequan Zhang; Tobias K.D. Weber; Elizabeth Pattey; Ziwei Li; Jiaxin Wang; Virginia L. Jin; et al. (Journal of Hydrology, 2025)

It's not all about PFAS: Metal(loid)s are associated with physiological and metabolic changes in a native frog from conservation wetlands - Damian C. Lettoof; Rui Wang; Brad Clarke; Nicola Gray; Samuele Sala; Nick Bourne; William R. Richmond; Helen E. Nice; Peter Novak; Brenton von Takach; Bruce L. Webber; Anna H. Kaksonen; et al. (Environmental Pollution, 2025)

Cold lenses in the Amundsen Sea: impacts of sea ice formation on subsurface pH and carbon - Daisy D. Pickup; Dorothee C. E. Bakker; Karen J. Heywood; Francis Glassup; Emily M. Hammermeister; Sharon E. Stammerjohn; Gareth A. Lee; Socratis Loucaides; Bastien Y. Queste; Benjamin G. M. Webber; Patricia L. Yager (Ocean Science, 2025)
The Amundsen Sea polynya hosts intense sea ice formation, but, due to the presence of relatively warm and salty modified Circumpolar Deep Water, the cold, brine-enriched water is not typically dense enough to sink to the deep ocean. A hydrographic survey of the Dotson Ice Shelf region in the Amundsen Sea using two ocean gliders identified and characterised subsurface lenses containing water with temperatures less than −1.70 °C. These lenses, located at depths between 240 to 500 m, were colder, saltier and denser than the overlying Winter Water (WW) layer. The pH of the lenses was 7.99, lower than WW by 0.02 and the dissolved inorganic carbon concentration was higher in the lenses than WW by approximately 10 µmol kg−1. The lenses were associated with a dissolved oxygen concentration greater than surrounding water at the same depth and density due to the cold temperatures increasing O2 solubility. We hypothesise that these lenses are a product of wintertime surface cooling and brine rejection in areas with intense sea ice formation. They may form in shallow regions, potentially around the Martin Peninsula and Bear Island, where intense upper ocean heat loss occurs, and then spill off into the deeper Dotson-Getz Trough to reach their neutrally-buoyant depth. This is supported by wintertime temperature and salinity observations. This study highlights the importance of shallow parts of shelf seas for generating cold dense water masses in the warm sector of Antarctica. These lenses are widespread in the region of the Dotson-Getz Trough and have the potential to sequester carbon deeper than typical in the region, alongside cooling the water impinging on the Dotson ice shelf base.

Wheat crop models underestimate drought stress in semi-arid and Mediterranean environments - H. Webber; D. Cooke; C. Wang; S. Asseng; P. Martre; F. Ewert; B. Kimball; G. Hoogenboom; S. Evett; A. Chanzy; S. Garrigues; A. Olioso; et al. (Field Crops Research, 2025)

Assessing the potential for building sector retrofits to mitigate ERCOT electricity shortfalls during Winter Storm Uri - Matthew J. Skiles; Justin Shih; Joshua D. Rhodes; Michael E. Webber (Energy and Buildings, 2025)

Social Microbial Transmission in a Solitary Mammal - Lauren Petrullo; Quinn Webber; Aura Raulo; Stan Boutin; Jeffrey E. Lane; Andrew G. McAdam; Ben Dantzer (Ecology Letters, 2025)
Microbial transmission is hypothesised to be a major benefit of sociality, facilitated by affiliative behaviours such as grooming and communal nesting in group‐living animals. Whether microbial transmission is also present in animals that do not form groups because territoriality limits interactions and prevents group formation remains unknown. Here, we investigate relationships among gut microbiota, population density and dynamic behavioural and spatial measures of territoriality in wild North American red squirrels ( Tamiasciurus hudsonicus ). Periods of high population density predicted population‐level gut microbial homogeneity but individual‐level diversification, alongside changes in obligately anaerobic, non‐sporulating taxa indicative of social transmission. Microbial alpha‐diversity increased with more frequent territorial intrusions, and pairs with stronger intrusion‐based social associations had more similar gut microbiota. As some of the first evidence for social microbial transmission in a solitary system, our findings suggest that fluctuations in density and territorial behaviours can homogenise and diversify host microbiomes among otherwise non‐interacting animals.

The economics of small modular reactors at coal sites: A program-level analysis within the state of Texas - Eric Wieser; Kevin Clarno; Derek Haas; Michael E. Webber (Energy Policy, 2025)

Consistent Individual Differences and Plasticity in Migration Behaviour of Three North American Ungulates - Michel P. Laforge; Eric Vander Wal; Quinn M. R. Webber; Chris Geremia; Matthew J. Kauffman; Douglas E. McWhirter; Arthur Middleton; Tony W. Mong; Kevin L. Monteith; Anna C. Ortega; Hall Sawyer; Jerod A. Merkle (Ecology Letters, 2025)
Migratory herbivores often time spring migration to coincide with the green‐up of plants. When the timing of green‐up changes across years, herbivores can respond directly and be plastic to changing conditions or populations may adapt via inherent differences among individuals that may allow for an evolutionary response. We quantified plasticity and individual variation in the timing of spring migration and selection for high‐quality forage as a function of the timing of spring green‐up using behavioural reaction norms for three North American ungulate species. The timing of arrival to summer range (but not departure from winter range) was plastic to the timing of green‐up, and both arrival and departure timing were repeatable. Our results suggest that herbivores synchronise migration with the timing of green‐up by adjusting the pace of migration and may be buffered against change via individual differences. Quantifying plasticity and differences in responses represents a crucial step to elucidating the fate of species in a changing world.

Avocado ( Persea americana Mill) and its phytoconstituents: potential for cancer prevention and intervention - Taylor E. Collignon; Kassidy Webber; Josh Piasecki; Austin S. W. Rahman; Arijit Mondal; Sandra Maria Barbalho; Anupam Bishayee (Critical Reviews in Food Science and Nutrition, 2024)

Simulation of soil temperature under maize: An inter-comparison among 33 maize models - Bruce A. Kimball; Kelly R. Thorp; Kenneth J. Boote; Claudio Stockle; Andrew E. Suyker; Steven R. Evett; David K. Brauer; Gwen G. Coyle; Karen S. Copeland; Gary W. Marek; Paul D. Colaizzi; Marco Acutis; et al. (Agricultural and Forest Meteorology, 2024)

Ensuring reliability: What is the optimal time for power plant maintenance in Texas as the climate changes? - Hugh Daigle; Joshua D. Rhodes; Aidan Pyrcz; Michael E. Webber (The Electricity Journal, 2024)

What Impact Does Participation in a Communication Skills Training Program Have on Health Professionals’ Communication Behaviors: Findings from a Qualitative Study - V. White; M. Chiswell; E. Webber; P. Martin; A. Piper (Journal of Cancer Education, 2023)
Communication skills training can enhance health professionals’ knowledge and repertoire of effective communication practices. This paper describes the conceptual model underlying a 3-day retreat communication skills training program, methods used for training, and participant perception of outcomes from the training using qualitative interviews. Repeated qualitative telephone interviews (approximately 6 months apart) with participants of a 3-day Clinical Consultation Skills Retreat. Fourteen participants (70% response, 57% doctors) took part at Time 1, with 12 participating at Time 2. Semi-structured interviews were recorded and transcribed, and directional content analysis was conducted to assess themes in areas of key learnings, implementation of skills, and barriers. The training was received very positively with participants valuing the small group learning, role play, and facilitator skills. Key learnings were grouped into two themes: (i) tips and strategies to use in clinical practice and (ii) communication frameworks/methods, with the second theme reflecting an awareness of different communication styles. Most participants had tried to implement their new skills, with implementation reported as a more deliberate activity at T1 than at T2. Those implementing the new skills noted more open conversations with patients. Practical barriers of lack of time and expectations of others were mentioned more often at T2. A 3-day retreat-based communication training program was positively received and had a positive impact on the use of new communication skills. While further work is needed to determine whether effects of training are evidenced in objective clinical behaviors, the positive longer-term benefits found suggest this work would be worthwhile.

Simulation of evapotranspiration and yield of maize: An inter-comparison among 41 maize models - Bruce A. Kimball; Kelly R. Thorp; Kenneth J. Boote; Claudio Stockle; Andrew E. Suyker; Steven R. Evett; David K. Brauer; Gwen G. Coyle; Karen S. Copeland; Gary W. Marek; Paul D. Colaizzi; Marco Acutis; et al. (Agricultural and Forest Meteorology, 2023)

Perspectives on peak demand: How is ERCOT peak electric load evolving in the context of changing weather and heating electrification? - Matthew J. Skiles; Joshua D. Rhodes; Michael E. Webber (The Electricity Journal, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Delta-9-tetrahydrocannabinol reduces willingness to exert effort in women - Margaret C. Wardle; Elisa Pabon; Heather E. Webber; Harriet de Wit (Psychopharmacology, 2022)

Progress in understanding of Indian Ocean circulation, variability, air–sea exchange, and impacts on biogeochemistry - Helen E. Phillips; Amit Tandon; Ryo Furue; Raleigh Hood; Caroline C. Ummenhofer; Jessica A. Benthuysen; Viviane Menezes; Shijian Hu; Ben Webber; Alejandra Sanchez-Franks; Deepak Cherian; Emily Shroyer; et al. (Ocean Science, 2021)
Over the past decade, our understanding of the Indian Ocean has advanced through concerted efforts toward measuring the ocean circulation and air–sea exchanges, detecting changes in water masses, and linking physical processes to ecologically important variables. New circulation pathways and mechanisms have been discovered that control atmospheric and oceanic mean state and variability. This review brings together new understanding of the ocean–atmosphere system in the Indian Ocean since the last comprehensive review, describing the Indian Ocean circulation patterns, air–sea interactions, and climate variability. Coordinated international focus on the Indian Ocean has motivated the application of new technologies to deliver higher-resolution observations and models of Indian Ocean processes. As a result we are discovering the importance of small-scale processes in setting the large-scale gradients and circulation, interactions between physical and biogeochemical processes, interactions between boundary currents and the interior, and interactions between the surface and the deep ocean. A newly discovered regional climate mode in the southeast Indian Ocean, the Ningaloo Niño, has instigated more regional air–sea coupling and marine heatwave research in the global oceans. In the last decade, we have seen rapid warming of the Indian Ocean overlaid with extremes in the form of marine heatwaves. These events have motivated studies that have delivered new insight into the variability in ocean heat content and exchanges in the Indian Ocean and have highlighted the critical role of the Indian Ocean as a clearing house for anthropogenic heat. This synthesis paper reviews the advances in these areas in the last decade.

Acute drug effects differentially predict desire to take dextroamphetamine again for work and recreation - Jennifer K. Hoots; Heather E. Webber; Cecilia Nunez; Jessica A. Cooper; Paula Lopez-Gamundi; Victoria M. Lawlor; Scott D. Lane; Michael T. Treadway; Margaret C. Wardle (Psychopharmacology, 2021)

Stokes drift through corals - Joseph J. Webber; Herbert E. Huppert (Environmental Fluid Mechanics, 2021)
Motivated by shallow ocean waves propagating over coral reefs, we investigate the drift velocities due to surface wave motion in an effectively inviscid fluid that overlies a saturated porous bed of finite depth. Previous work in this area either neglects the large-scale flow between layers (Phillips in Flow and reactions in permeable rocks, Cambridge University Press, Cambridge, 1991) or only considers the drift above the porous layer (Monismith in Ann Rev Fluid Mech 39:37–55, 2007). Overcoming these limitations, we propose a model where flow is described by a velocity potential above the porous layer and by Darcy’s law in the porous bed, with derived matching conditions at the interface between the two layers. Both a horizontal and a novel vertical drift effect arise from the damping of the porous bed, which requires the use of a complex wavenumber k . This is in contrast to the purely horizontal second-order drift first derived by Stokes (Trans Camb Philos Soc 8:441–455, 1847) when working with solely a pure fluid layer. Our work provides a physical model for coral reefs in shallow seas, where fluid drift both above and within the reef is vitally important for maintaining a healthy reef ecosystem (Koehl et al. In: Proceedings of the 8th International Coral Reef Symposium, vol 2, pp 1087–1092, 1997; Monismith in Ann Rev Fluid Mech 39:37–55, 2007). We compare our model with field measurements by Koehl and Hadfield (J Mar Syst 49:75–88, 2004) and also explain the vertical drift effects as documented by Koehl et al. (Mar Ecol Prog Ser 335:1–18, 2007), who measured the exchange between a coral reef layer and the (relatively shallow) sea above.

Invasion trajectory of alien trees: the role of introduction pathway and planting history - Jason E. Donaldson; Cang Hui; David M. Richardson; Mark P. Robertson; Bruce L. Webber; John R.U. Wilson (Global Change Biology, 2014)
Global change is driving a massive rearrangement of the world's biota. Trajectories of distributional shifts are shaped by species traits, the recipient environment and driving forces with many of the driving forces directly due to human activities. The relative importance of each in determining the distributions of introduced species is poorly understood. We consider 11 Australian Acacia species introduced to South Africa for different reasons (commercial forestry, dune stabilization and ornamentation) to determine how features of the introduction pathway have shaped their invasion history. Projections from species distribution models ( SDM s) were developed to assess how the reason for introduction influences the similarity between climatic envelopes in native and alien ranges. A lattice model for an idealized invasion was developed to assess the relative contribution of intrinsic traits and introduction dynamics on the abundance and extent over the course of simulated invasions. SDM s show that alien populations of ornamental species in South Africa occupy substantially different climate space from their native ranges, whereas species introduced for forestry occupy a similar climate space in native and introduced ranges. This may partly explain the slow spread rates observed for some alien ornamental plants. Such mismatches are likely to become less pronounced with the current drive towards ‘eco gardens’ resulting in more introductions of ornamental species with a close climate match between native and newly introduced regions. The results from the lattice model showed that the conditions associated with the introduction pathway (especially introduction pressure) dominate early invasion dynamics. The placement of introduction foci in urban areas limited the extent and abundance of invasive populations. Features of introduction events appear to initially mask the influence of intrinsic species traits on invasions and help to explain the relative success of species introduced for different purposes. Introduction dynamics therefore can have long‐lasting influences on the outcomes of species redistributions, and must be explicitly considered in management plans.

Cumulative geoecological effects of 62 years of infrastructure and climate change in ice‐rich permafrost landscapes, Prudhoe Bay Oilfield, Alaska - Martha K. Raynolds; Donald A. Walker; Kenneth J. Ambrosius; Jerry Brown; Kaye R. Everett; Mikhail Kanevskiy; Gary P. Kofinas; Vladimir E. Romanovsky; Yuri Shur; Patrick J. Webber (Global Change Biology, 2014)
Many areas of the Arctic are simultaneously affected by rapid climate change and rapid industrial development. These areas are likely to increase in number and size as sea ice melts and abundant Arctic natural resources become more accessible. Documenting the changes that have already occurred is essential to inform management approaches to minimize the impacts of future activities. Here, we determine the cumulative geoecological effects of 62 years (1949–2011) of infrastructure‐ and climate‐related changes in the Prudhoe Bay Oilfield, the oldest and most extensive industrial complex in the Arctic, and an area with extensive ice‐rich permafrost that is extraordinarily sensitive to climate change. We demonstrate that thermokarst has recently affected broad areas of the entire region, and that a sudden increase in the area affected began shortly after 1990 corresponding to a rapid rise in regional summer air temperatures and related permafrost temperatures. We also present a conceptual model that describes how infrastructure‐related factors, including road dust and roadside flooding are contributing to more extensive thermokarst in areas adjacent to roads and gravel pads. We mapped the historical infrastructure changes for the Alaska North Slope oilfields for 10 dates from the initial oil discovery in 1968–2011. By 2010, over 34% of the intensively mapped area was affected by oil development. In addition, between 1990 and 2001, coincident with strong atmospheric warming during the 1990s, 19% of the remaining natural landscapes (excluding areas covered by infrastructure, lakes and river floodplains) exhibited expansion of thermokarst features resulting in more abundant small ponds, greater microrelief, more active lakeshore erosion and increased landscape and habitat heterogeneity. This transition to a new geoecological regime will have impacts to wildlife habitat, local residents and industry.

Clean energy and water: assessment of Mexico for improved water services and renewable energy - Kelly T. Sanders; Carey W. King; Ashlynn S. Stillwell; Michael E. Webber (Environment, Development and Sustainability, 2013)

Latitudinal variation in blue tit and great tit nest characteristics indicates environmental adjustment - Mark C. Mainwaring; Ian R. Hartley; Stuart Bearhop; Kaat Brulez; Christopher R. du Feu; Gerald Murphy; Kate E. Plummer; Simone L. Webber; S. James Reynolds; D. Charles Deeming (Journal of Biogeography, 2012)
Aim The laying of eggs and the building of a nest structure to accommodate them are two of the defining characteristics of members of the class Aves. Nest structures vary considerably across avian taxa and for many species the structure of the completed nest can have important consequences both for parents and their offspring. While nest characteristics are expected to vary adaptively in response to environmental conditions, large‐scale spatial variation in nest characteristics has been largely overlooked. Here, we examine the effects of latitudinal variation in spring temperatures on nest characteristics, including insulatory properties, and reproductive success of blue tits, Cyanistes caeruleus , and great tits, Parus major . Location Great Britain. Methods Nests and reproductive data were collected from seven study sites, spread over 5° of latitude. The nest insulatory properties were then determined before the nests were separated into nest base material and cup lining material. Results As spring temperatures increased with decreasing latitude, the mass of the nest base material did not vary in either species, while the mass of the cup lining material and nest insulatory properties decreased in both species. This suggests that in response to increasing temperatures the breeding female reduces the mass of the cup lining material, thereby maintaining an appropriate microclimate for incubating and brooding. The mean first egg date of both species advanced with decreasing latitude and increasing spring temperatures, although clutch size and brood size at hatching and fledging did not vary. Main conclusions This is the first study to demonstrate that the nest‐construction behaviour of birds varies in response to large‐scale spatial variation in ambient temperatures. Therefore, nest composition reliably indicates environmental conditions and we suggest that studies of nest structure may be sentinels for the early signs of rapid climate change.

The Energy Return on Investment for Algal Biocrude: Results for a Research Production Facility - Colin M. Beal; Robert E. Hebner; Michael E. Webber; Rodney S. Ruoff; A. Frank Seibert (BioEnergy Research, 2012)

Energy expenditure during egg laying is equal for early and late breeding free-living female great tits - Luc te Marvelde; Simone L. Webber; Harro A. J. Meijer; Marcel E. Visser (Oecologia, 2012)

Forecasting Alpine Vegetation Change Using Repeat Sampling and a Novel Modeling Approach - David R. Johnson; Diane Ebert-May; Patrick J. Webber; Craig E. Tweedie (Ambio, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Multi-decadal Changes in Tundra Environments and Ecosystems: The International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Patrick J. Webber (Ambio, 2011)

A Framework to Report the Production of Renewable Diesel from Algae - Colin M. Beal; Colin H. Smith; Michael E. Webber; Rodney S. Ruoff; Robert E. Hebner (BioEnergy Research, 2011)

Influence of urban tributaries on freshwater mussel populations in a biologically diverse piedmont (USA) stream - Michael M. Gangloff; Lynn Siefferman; Wendy Seesock; E. Cliff Webber (Hydrobiologia, 2009)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

The response of Alaskan arctic tundra to experimental warming: differences between short‐ and long‐term responses - Robert D. Hollister; Patrick J. Webber; Craig E. Tweedie (Global Change Biology, 2005)
Global climate models predict continued rapid warming for most of the Arctic throughout the next century. To further understand the response of arctic tundra to climate warming, four sites in northern Alaska were warmed for five to seven consecutive growing seasons using open‐top chambers. Sites were located in dry heath and wet meadow communities near Barrow (71°18′N, 156°40′W) and Atqasuk (70°29′N, 157°25′W). Change in plant community composition was measured using a point frame method. During the period of observation, species richness declined in control plots by up to 2.7 species plot −1 . Responses to warming varied by site but similar trends included increased canopy height (−0.1 to 2.3 cm) and relative cover of standing dead plant matter (1.5–6.0%) and graminoids (1.8–5.8%) and decreased species diversity (0.1–1.7 species plot −1 ) and relative cover of lichens (0.2–9.1%) and bryophytes (1.4–4.6%) (parentheses enclose the range of average values for the sites). The response to warming was separated into an initial short‐term response assessed after two growing seasons of warming and a secondary longer‐term response assessed after an additional three to five growing seasons of warming. The initial responses to warming were similar in the four sites, while the secondary responses varied by site. The response to warming was greater at Barrow than Atqasuk because of a greater initial response at Barrow. However, the long‐term response to warming was projected to be greater at Atqasuk because of a greater secondary response at Atqasuk. These findings show that predictions of vegetation change due to climate warming based on manipulative experiments will differ depending on both the duration and plant community on which the study focuses.

High irradiance increases organogenesis in friable callus of Caustis blakei Kük. (Cyperaceae) - Julie Webber; Margaret E. Johnston; Alan H. Wearing (In Vitro Cellular & Developmental Biology - Plant, 2003)

A whole-genome radiation hybrid panel and framework map of the rat genome - Linda C. McCarthy; Marie-Therese Bihoreau; Susanna L. Kiguwa; Julie Browne; Takeshi K. Watanabe; Haretsugu Hishigaki; Atsushi Tsuji; Susanne Kiel; Caleb Webber; Maria E. Davis; Catherine Knights; Angela Smith; et al. (Mammalian Genome, 2000)

Seed cone production enhanced by injecting 38-year-old Larix occidentalis Nutt. with GA4/7 - Raymond C. Shearer; Michael U. Stoehr; Joe E. Webber; Stephen D. Ross (New Forests, 1999)

Excitation energy transfer in thylakoid membranes from Chlamydomonas reinhardtii lacking chlorophyll b and with mutant Photosystem I - Alexander N. Melkozernov; Hui Su; Andrew N. Webber; Robert E. Blankenship (Photosynthesis Research, 1998)

Fluorescence study of the core/shell interface in polyelectrolyte micelles. Binding of fluorescent surfactants in the interfacial region - KateŘina Krijtová; Miroslav štĚpánek; Karel Procházka; Stephen E. Webber (Journal of Fluorescence, 1998)

A comparison of strength and muscle mass increases during resistance training in young women - Philip D. Chilibeck; Aaron W. Calder; Digby G. Sale; Colin E. Webber (European Journal of Applied Physiology, 1997)

DDT contamination of benthic macroinvertebrates and sediments from tributaries of Wheeler Reservoir, Alabama - E. Cliff Webber; D. R. Bayne; W. C. Seesock (Archives of Environmental Contamination and Toxicology, 1989)

An improved multi-element measurement of mineral absorption in the piglet utilizing the fecal monitoring technique - Rosalind S. Gibson; Ian L. Gibson; Colin E. Webber; Stephanie A. Atkinson (Biological Trace Element Research, 1988)

?-Thalassemia and the production of different ? chain variants in heterozygotes - A. E. Felice; B. B. Webber; T. H. J. Huisman (Biochemical Genetics, 1981)